Discovery and validation of serum glycoprotein biomarkers for high grade serous ovarian cancer - Dutt, Mriga (Proteomics Clin Appl, 2023)
PURPOSE: This study aimed to identify serum glycoprotein biomarkers for early detection of high‐grade serous ovarian cancer (HGSOC), the most common and aggressive histotype of ovarian cancer. EXPERIMENTAL DESIGN: The glycoproteomics pipeline lectin magnetic bead array (LeMBA)‐mass spectrometry (MS) was used in age‐matched case‐control serum samples. Clinical samples collected at diagnosis were divided into discovery (n = 30) and validation (n = 98) sets. We also analysed a set of preclinical sera (n = 30) collected prior to HGSOC diagnosis in the UK Collaborative Trial of Ovarian Cancer Screening. RESULTS: A 7‐lectin LeMBA‐MS/MS discovery screen shortlisted 59 candidate proteins and three lectins. Validation analysis using 3‐lectin LeMBA‐multiple reaction monitoring (MRM) confirmed elevated A1AT, AACT, CO9, HPT and ITIH3 and reduced A2MG, ALS, IBP3 and PON1 glycoforms in HGSOC. The best performing multimarker signature had 87.7% area under the receiver operating curve, 90.7% specificity and 70.4% sensitivity for distinguishing HGSOC from benign and healthy groups. In the preclinical set, CO9, ITIH3 and A2MG glycoforms were altered in samples collected 11.1 ± 5.1 months prior to HGSOC diagnosis, suggesting potential for early detection. CONCLUSIONS AND CLINICAL RELEVANCE: Our findings provide evidence of candidate early HGSOC serum glycoprotein biomarkers, laying the foundation for further study in larger cohorts.